Fibromodulin Ablation Exacerbates the Severity of Acute Colitis - Halasi M; Grinstein M; Adini A; Adini I (Dove Medical Press, 2022)
Marianna Halasi,1 Mor Grinstein,2 Avner Adini,3 Irit Adini1 1Department of Surgery, Center for Engineering in Medicine & Surgery, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 2Department of Medicine, Center for Regenerative Medicine, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 3Department of Medicine, Boston Children's Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Irit Adini, Email iadini@mgh.harvard.eduIntroduction: Epidemiological studies have associated pigment production with protection against certain human diseases. In contrast to African Americans, European descendants are more likely to suffer from angiogenesis-dependent and inflammatory diseases, such as wet age-related macular degeneration (ARMD) and ulcerative colitis (UC), respectively.Methods: In a mouse model of dextran sulfate sodium (DSS)-induced acute colitis, the effect of fibromodulin (FMOD) depletion was examined on colitis severity.Results: In this study, albino mice that produce high levels of FMOD developed less severe acute colitis compared with mice lacking in FMOD as assessed by clinical symptoms and histopathological changes. FMOD depletion affected the expression of tight junction proteins, contributing to the destruction of the epithelial barrier. Furthermore, this study revealed a stronger inflammatory response after DSS treatment in the absence of FMOD, where FMOD depletion led to an increase in activated T cells, plasmacytoid dendritic cells (pDCs), and type I interferon (IFN) production.Discussion: These findings point to FMOD as a potential biomarker of disease severity in UC among light-skinned individuals of European descent.Keywords: inflammatory bowel disease, ulcerative colitis, fibromodulin, tight junction, dendritic cells